EVALUACIÓN CLÍNICA DEL GRABADO ÁCIDO "ACID ETCHING" - Lahoud S., Víctor (2000)
The presents investigation shows the results of 480 cavities, trested with and without acid descalcification, during a control period of 18 months. The total of cavities were dividid acording its retention (microretention and without microretention observing marginal integrity in cavities with microretention specialy class III cavities), cavities class V with or without microretention show anfaurable results.